FEATURES OF ORGANIZATION MANAGERS’ PROFESSIONAL STRESS EPISODES - Stelmashchuk, Khrystyna (PSYCHOLOGICAL JOURNAL, 2019)
Presently, the problem of occupational stress is especially acute and the impact of professional work on the health of managers/business leaders, whose work is closely related to managerial duties and is characterised by a high level of responsibility, making difficult decisions, intense and emotional interactions with people, has become the most studied one. Thus, occupational stress is an employee’s stress state under influences of emotionally negative and extreme factors associated with his/her professional duties; this is a multidimensional phenomenon, manifested in mental and somatic reactions to stressful situations during labour activities. Any stress, including professional one, is experiences by a person via the structure of a stressful episode. If we consider the structure of a manager’s stressful episode, then, first of all, it is necessary to describe stressful factors affect him/her most of all. So, any factor can become a source of professional stress for a manager: political, social, human. Yu. Shcherbatykh names the following main stressful factors for managers of different levels: 1. The complexity and inconsistency of the legislation and regulatory instructions; 2. Low motivation of employees and the need for constant monitoring of their work; 3. Absence of mutual understanding with business partners and conflicts with them, a constant lack of time; 4. Excessive and not always justified control by administration (government officials and heads of subsidiaries); 5. A feeling of discrepancy between applied efforts and actual results; 6. Loss of meaning of work; 7. Stress of unfulfilled hopes. In the modern Ukrainian realities, managers and business leaders face some additional significant stressors, namely: 1. The shortage of skilled workers due to mass emigration to EU countries, hence the problem of staff selection; 2. Unstable political changes, politicization of power and business. For this reason, the business sectors having representatives in power are being lobbied, and managers have to search a balance in these conditions and think how to stay in advantageous positions. 3. Rapid changes in supply / demand trends in the market, a sense of a client’s market; constant monitoring of a client’s needs and the desire to always keep abreast and keep pace with ongoing changes; 4. Interactions with a large number of people from various fields (clients; staff accountants; notaries and lawyers, representatives of various regulatory bodies (the State Fiscal Service of Ukraine, the State Labour Service of Ukraine, the State Communal Bureau of Technical Inventory, etc.) concerning the issues in which managers themselves are sometimes incompetent, however, solutions are required; 5. Analysis of payables and receivables; 6. The pressure of responsibility for decisions made, and realization that a manager’s decisions can sometimes affect the emotional or material well-being of people who work near; and many others. Therefore, the structure of a manager’s stressful episode should be widened on the basis of the studies of C. Wage, C. Tavris, and include a leader’s / manager’s individual interpretations of events or a situation. Actually, such individual assessment of events is formed both taking into account the characteristics of a situation, and personality characteristics of a person (his/her motives, goals, values ​​...). An emotional or rational component can prevail in such an assessment. Jr. Everly and R. Rosenfeld also believe that during most stimuli (external or internal) conversion into stressors, their emotional and mental assessment plays a role. Thus, stressful reactions are mostly created by a person him/herself and last as long as they are allowed to. Also, dysfunctional patterns of human thinking should be taken into account at analysis of a manager’s stressful episode. As noted by A. Ellis, a dysfunctional reaction to a stressful event can occur due to a false, automatic, habitual response or due to a lack of experience of an adequate response. There can also be a discrepancy between knowing what is needed and knowing how to achieve it. In addition, the beliefs that a person uses in a stressful situation can be dysfunctional by their nature. The next important point is how an individual copes with stress. Not every person under stress behaves as usual. Indeed, under a strong psycho-traumatic factor, not so much situation assessment, but rather a person’s sharp emotional reaction to the events plays the main role in a distress state (most often an affect). And such strong emotions, appearing during stressful situations of a manager’s work, often prevent him/her from adequate assessment of the situation and constructive actions. Accordingly, the last components of a stressful episode are psychological defence mechanisms and coping strategies, and their result is adaptation or maladaptation to the stressful situation.